If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 + -12x = 4x + -13 + -5y Reorder the terms: 9 + 8x + -12x = 4x + -13 + -5y Combine like terms: 8x + -12x = -4x 9 + -4x = 4x + -13 + -5y Reorder the terms: 9 + -4x = -13 + 4x + -5y Solving 9 + -4x = -13 + 4x + -5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + -4x + -4x = -13 + 4x + -4x + -5y Combine like terms: -4x + -4x = -8x 9 + -8x = -13 + 4x + -4x + -5y Combine like terms: 4x + -4x = 0 9 + -8x = -13 + 0 + -5y 9 + -8x = -13 + -5y Add '-9' to each side of the equation. 9 + -9 + -8x = -13 + -9 + -5y Combine like terms: 9 + -9 = 0 0 + -8x = -13 + -9 + -5y -8x = -13 + -9 + -5y Combine like terms: -13 + -9 = -22 -8x = -22 + -5y Divide each side by '-8'. x = 2.75 + 0.625y Simplifying x = 2.75 + 0.625y
| N*4=15-N | | 6.9x-1.6=12.2 | | 1/4×1/4÷1/4 | | 4/3x-8=0 | | A^2-2a+6=-7a | | 5(6z-1)-2(z+3)=20(z+1) | | 1/4×1/4×1/4 | | 5+9(x-3)=8-7(x-2) | | (x-y)(xr-xs-ys+yt)=(x+y)(p-q) | | 4x-5y+7z=2 | | 20-14=u | | 5/1x=6/5 | | y=-6/2=1 | | 14x^2/14x | | 2x^2-70x+600=0 | | 16x+43-39x=11 | | 7=2+g | | (x+1)(x-i)(x+i)=0 | | 2-2y=-8x | | 8+2x+3-x=2x+4 | | (12+X)X=36 | | (x-5)(xi)(x+i)=0 | | 8(2)+y=7 | | 4m^3-24m^2+100m= | | A^2-28=3a | | 15*.6=.7x+.4y | | 19x+5+8x=5 | | 11t+8+4t=20 | | R^2-29-2r=7-2r | | 448x^4-63x^2y^2= | | 4.36t=6.2 | | (2000-3P)XP=2000P-3P^2 |